SIGNIFICANCE OF NUMBERS IN HUMAN LIFE (British Journal of Global Ecology and Sustainable Development, 2023)
This article analyzes the importance of numbers in our lives. It is considered that the number is one of the first mathematical knowledge known to primitive mankind. Numbers, which are interpreted as simple mathematical symbols, are in fact a priceless treasure that shows the culture, national mentality, tradition and daily life of an entire nation. Many secrets are stored in the numbers, which serve to reveal the national spirituality of each nation. The article contains information about the history of numbers, their role in world civilization and the attitude to numbers in the modern world, as well as the study of numbers from a numerological aspect.